Experimental Study of Critical Rainfall of the Aizi Gully Baihetan Hydropower Station Near-Zone Area (International Journal of Scientific Research and Management (IJSRM), 2016)
At dawn of 28 June 2012, a catastrophic debris flow occurred in Aizi gully near Baihetan hydropower station, resulting in 40 people dead or missing. In addition, the debris flow blocked the main transportation route of Baihetan hydropower station and severely affected the construction progress. After the catastrophic debris flow event, detailed field investigations were conducted. By means of the field investigation, the corresponding catchment parameters that prominently affected the process of debris flow formation were acquired, including the volume and distribution of loose solid materials in the source area, meteorological conditions, topography and landforms, etc. On the basis of field investigations, we predicted that Aizi gully still satisfies debris flows initiation conditions and poses a great possibility for debris flow breakout in the future. Therefore, sufficient accurate prediction and forecasting are the precondition for disaster mitigation and siting mitigation structures in Aizi gully. At present, critical rainfall plays a key role in debris flows prediction. Thus, the main objective of this paper is to obtain the critical rainfall of Aizi gully. An in-situ artificial rainfall experiments were conducted in Aizi gully catchment, and by means of analyzing the experimental results (rainfall, pore water pressure and moisture content) and comprehensively considering the local rainfall conditions, the critical rainfall and pore water pressure of Aizi gully is acquired. The critical rainfall is 32.92mm/24h (accumulative rainfall). On the basis of this threshold, an early warning system can be established in Aizi gully catchment. Thus in turn, the warning information can be released in a timely and accurate way and can reduce the threat caused by debris flow disasters. At the same time, the safety of the construction processes of Baihetan hydropower station can be guaranteed